Comparison of Infection Rate in Buried vs. Exposed Ends of K-wire Used in Fixation of Pediatric Supracondylar Humerus Fracture - Qasim, Muhammad; Wali, Awais; Shafi ul Haq; Waqar, Muhammad (Indus Journal of Bioscience Research, 2025)
Objectives: This study aims to compare the rate of pin site infection in pediatric supracondylar fracture fixation in exposed vs. buried K-wire tips. Methodology: This prospective study was conducted at Orthopedic and spine unit MTI-HMC, Peshawar from January 2023 to December 2023. This study included 50 pediatric patients that were treated with closed reduction and percutaneous pinning for displaced supracondylar humerus fracture. Patients were followed from fist post-operative till removal of K-wire at 03 weeks for any pin site infection. Data was then recorded, analyzed and presented in percentages. Results: Patient with Expose K-wires end were assigned group 1 while buried K-wire ends group was assigned as group 2. 07(14.9%) out of 47 patients in Group 1 developed superficial infection. while 06(14.3%) out of 42 patients in group 2 developed superficial infection. K-wires in group 1 were removed in outpatient department without sedation while K-wires in group 2 were removed Operation Theater under sedation. Infection in both groups was managed with oral antibiotics. Conclusion: Infection at pin sites in exposed K-wire ends group was slightly more as compared to buried K-wires end group but they were managed easily with oral antibiotics. Removal of K-wires in buried K-wire ends group required second surgery. Thus, leaving K-wire ends outside skin after fixation of displaced supracondylar humerus fracture is more convenient and cost-effective technique for patient, family and hospital.